Beyond loving intimate racework in lesbian, gay, and straight interracial relationships - Steinbugler, Amy C. (New York ; Oxford : Oxford University Press, 2012)
In this work, Amy Steinbugler challenges the widespread assumption that interracial intimacy represents the ultimate erasure of racial differences. She finds that while interracial partners may be more racially progressive, they are not necessarily enlightened subjects who have managed to get beyond race.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Gay couples; Lesbian couples; Heterosexuals; Interracial marriage; Race relations; Race awareness